Implementation of Blockchain Technology to Improve Transparency and Accountability in the Mineral Supply Chain - Kasmira Kasmira (Journal of Tecnologia Quantica, 2025)
This study analyzes the potential and challenges of implementing blockchain technology to enhance transparency, accountability, and traceability in mineral supply chains. Using a qualitative approach with case-study methods and thematic analysis of interviews, company reports, regulatory documents, and scientific literature, the study compares initiatives by several industry actors. The findings show that blockchain strengthens end?to?end provenance tracking, authenticity verification, compliance with environmental and ethical standards, and minimizes data manipulation and illicit trade practices. In addition, blockchain integration drives operational efficiency and inter?stakeholder trust through immutable, auditable transaction logs. However, adoption faces structural barriers in the form of regulatory uncertainty, limited digital infrastructure in developing countries, and organizational resistance to system change. This study recommends establishing clear regulatory frameworks, public–private collaboration, cross?platform data standardization, and capacity building including integration with IoT and digital identity to maximize blockchain’s impact on more sustainable and responsible governance of mineral supply chains.